Time-variant fatigue reliability evaluation of riveted lap joint under stationary random loading. (August 2020) - Jiang, Shan; Li, Yan-Fu
This article focuses on the time-variant reliability assessment of riveted lap joint structure subjected to fatigue. A physics-based fatigue crack growth model that can take the crack closure into account is derived to calculate the crack length at different time under arbitrary loading. In addition, several uncertainties are quantified, including the material, initial crack size, and loading condition. The stationary random loading is a common service environment in practice, in which the stress range and stress ratio vary with constant statistical characteristics (the mean and standard deviation). The time-variant fatigue reliability of riveted lap joint under stationary random loading is assessed by introducing the outcrossing concept. The experimental data of 2024-T3 aluminum alloy riveted lap joint under constant amplitude loading are used to validate the physics-based fatigue crack growth model. It is verified that this proposed model can predict the fatigue life probability distribution with a reasonable accuracy. In addition, the simulation of riveted lap joint under stationary random loading is performed. The time-variant fatigue reliability is evaluated. The results with or without considering crack closures are also compared. It is noted that the results from the time-variant fatigue reliability assessment considering crack closure has higher reliability level.